Karakteristik dan Sistem Pendidikan Islam: Mengenal Sejarah Pesantren, Surau dan Meunasah di Indonesia - Saeful Anam (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
Islam has expanded its wings to the archipelago of the seventeenth century and is believed to have progressed in the 13th century. The process of Islamization by predecessors requires media as a mediator of Islamic teach-ings. Pesantren, Surau and meunasah are the real proofs of Islamization that happened, where the three places of Islamic education as well as the medium of dakwah is a relic of ancestors whose existence precedes Islam in Indonesia. However, after the coming of Islam, the three centers of education are very instrumental in the Islamization of indigenous people, not stop in Islamization, but more than that; As a bastion and promoter of Indonesian independence during the Dutch colonial period (1800-1942) and Japan (1942-1945). The development of the three traditional education centers is very different pesantren better known in Java, Surau in Minangkabau while Meunasah in Aceh. Although geographically very different but in the essence of his teachings have in common that begins with learning the Qur'an and continues on Ubudiyah.Keywords;Â education system, Pesantren, Surau, Munasah